REDUKCJA WYRAZÓW PODOBNYCH
zad:Sprowadź wyrażenia do najprostszej postaci:

a) 13e-5(f-3e)=..........
b) 4(-2r+s)-10,5r=........
c) -3(3x-2y)+2(x-2y)=.........
d)-5(2z-3y)-4(4z-2y)=...........
e) 2(2p-3q+7)-3(p-2q+4)=...................................
f) 2(3x²-2y+5y²)-3(4y+5y²)+2x-3x²=...............................

Proszę o szybką pomoc! Z góry dziękuję

3

Odpowiedzi

2009-11-23T16:55:50+01:00
A) = 13e -5f + 15 e = 28e-5f
b) =-8r + 4s - 10,5r = -18,5r+4s
c) = -9x + 6y + 2x - 4y = -7x+2y
d) - 10z+15y-16z+8y=-26z+23y=23y-26z
e) =4p -6q+14-3p+6q-12=p-12
f) = 6x2 -4y+10y2-12y-15y2+2x-3x2=2x-16y+3x2-5y2
prosz.
Najlepsza Odpowiedź!
2009-11-23T16:57:22+01:00
A) 13e-5(f-3e)= 13e-5f+15e=28e-5f
b) 4(-2r+s)-10,5r= -8r+4s-10,5r=-18,5r+4s
c) -3(3x-2y)+2(x-2y)= -9x +6y +2x-4y=-7x+2y
d) -5(2z-3y)-4(4z-2y)= -10z+15y-16z+8y=-2y-z
e) 2(2p-3q+7)-3(p-2q+4)= 4p-6q+14-3p+6q-12=p+2 [6q-6q sie redukuje]
f) 2(3x²-2y+5y²)-3(4y+5y²)+2x-3x²= 6x²-4y+10y²-12y-15y²+2x-x²= 5x²-16y-5y²+2x
2009-11-23T16:58:00+01:00
A) 13e-5f+15e=28e-5f
b) -8r+4s-10,5r=-18,5r +4s
c) -9x+6y+2x-4y=-7x+2y
d) -10z+15y-16z+8y=-26z+23y
e)4p-6q+14-3p+6q-12=p+2
f) 6x²-4y+10y²-12y+10y²-15y²+2x-3x²=3x²-16y+5y²+2x